Determination of the Activity of an Experimental Anti-choleric Immunoenterosorbent in Vitro in Dot-immunoanalysis - M. V. Ovchinnikova; E. G. Abramova; M. N. Kireev; T. Yu. Kirillova; N. A. Sharapova; V. V. Rogozhin (Разработка и регистрация лекарственных средств)
Introduction. At the rate of World health organization from 1 to 4 million people annually get infected with cholera, and around 143 000 people become a victim of this infection. At this point of seventh pandemic WHO and its partners actively evaluate new methods of treatment and prevention of cholera in addition to existing traditional methods. Today enterosorbents are widely used for treatment and prevention of number of infectious diseases of the gastrointestinal tract. Previously reported about results of construction of specific enterosorbent, which having a neutralizing effect regard to choleric enterotoxin. For toxin-neutralizing activity of components and finalized product control applied Craig dermal test method, which have significant disadvantages: duration of analysis, using expensive biomodels, etc. Ethical side of in vivo methods is also important, which dictating necessity of experiment humanization and replacing mammals to less evolved living objects, using physicochemical and immunochemical systems.Aim. Methodical approach improvement of definition activity of semi-finalized and completed enterosorbent product in indirect in dot-immunoanalysis (DIA) with using non-enzymatic diagnosticum based on colloidal gold nanoparticles.Materials and methods. Were used antitoxic rabbit immunoglobulins and experimental series of anicholeraic immunoenterosorbent. Definition of toxin-neutralizing activity carried out by Craig test on adult rabbits. In indirect DIA were used hydrosol gold, connected with staphylococcus protein A by sorption and stabilized with solution PEG-20000.Results and discussion. In indirect DIA identified titers of specific antibody in product component samples composed from 1 : 6400 to 1 : 12800, while in copleted enterosorbent the titers composed from 1 : 6400 to 1 : 25600. Specificity of test is confirmed by negative results with standard rabbit immunoglobulins. Comparative analysis of toxin-neutralizing activity level of antitoxin immunoglobulins and anicholeraic enterosorbent, determined in Craig dermal test and DIA was performed: the correlation coefficient composed 0,93 and 0,97 respectively.Conclusion. Developed methodical approaches to indirect DIA conduction with S. aureus protein A based diagnosticum and colloidal gold nanoparticles can be used for determination of antitoxic activity level of immunoglobulins and experimental immunoenterosorbent. Correlation of in vitro and in vivo tests allows to recommend indirect DIA on control stages during specific anticholeraic enterosorbent production.